2018
DOI: 10.1111/cdev.13133
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Well‐Being Decreasing With Age: New Research on Children Over 8

Abstract: An increasing number of scientific publications have provided data from different countries suggesting subjective well-being (SWB) continuously decreases during adolescence. A review of these publications reveals authors have used dissimilar scales in diverse countries. Using data from the international Children's Worlds project (N = 48,040), involving 15 countries, a comparative analysis was performed to determine how mean scores evolve with different SWB scales from the age of 8 onwards. The results support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
86
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 50 publications
14
86
2
2
Order By: Relevance
“…Estos resultados coinciden con el estudio nacional anterior (Fernández et al, 2018) y al diferenciar el tramo de adolescencia tardía hasta los 21 años, puede observarse aún mejor la tendencia del nivel de BPS en las transiciones dentro de la propia adolescencia. Estos resultados coinciden con estudios internacionales que evidencian que conforme avanza la edad, el BPS disminuye (Alfaro et al, 2016;Casas & González-Carrasco, 2019;Casas, González, Figuer & Malo, 2009;Lin & Yi, 2018;Petito & Cummins, 2000;Varela et al, 2018). Las posibles explicaciones a este hallazgo se centran en que los cambios frecuentes a los que se enfrentan los adolescentes, tanto emocionales, físicos y también los desafíos sociales y a nivel académico podrían provocar un mayor nivel de estrés y terminar afectando su nivel de BPS (Lin & Yi, 2018).…”
Section: Discussionunclassified
“…Estos resultados coinciden con el estudio nacional anterior (Fernández et al, 2018) y al diferenciar el tramo de adolescencia tardía hasta los 21 años, puede observarse aún mejor la tendencia del nivel de BPS en las transiciones dentro de la propia adolescencia. Estos resultados coinciden con estudios internacionales que evidencian que conforme avanza la edad, el BPS disminuye (Alfaro et al, 2016;Casas & González-Carrasco, 2019;Casas, González, Figuer & Malo, 2009;Lin & Yi, 2018;Petito & Cummins, 2000;Varela et al, 2018). Las posibles explicaciones a este hallazgo se centran en que los cambios frecuentes a los que se enfrentan los adolescentes, tanto emocionales, físicos y también los desafíos sociales y a nivel académico podrían provocar un mayor nivel de estrés y terminar afectando su nivel de BPS (Lin & Yi, 2018).…”
Section: Discussionunclassified
“…From the limited previous studies regarding adolescent life satisfaction trajectories, evidence suggests that adolescence is often accompanied by a prominent drop in life satisfaction (Goldbeck et al, 2007;Moksnes & Espnes, 2013;Ullman & Tatar, 2001;Willroth et al, 2020). Negative trajectories throughout this time have also been evidenced for mood, depression or psychopathology (Bradford et al, 2002;Casas & González-Carrasco, 2019;González-Carrasco et al, 2017;Kwong et al, 2019;Singh et al, 2015). The literature investigating adolescent mental health changes has highlighted the need to account for gender differences when probing such wellbeing trajectories (Chui & Wong, 2016).…”
Section: Adolescent Life Satisfactionmentioning
confidence: 99%
“…First, the drop in life satisfaction scores during adolescence could be driven by conditions of life getting worse during this period, which in turn decreases how satisfied adolescents are with their life. While life satisfaction is not completely subsumed into mental health, well-mapped mental health trends in adolescence show increases in mental disorders such as depression or anxiety and decreases in other forms of subjective wellbeing (Bradford et al, 2002;Casas & González-Carrasco, 2019;González-Carrasco et al, 2017;Kwong et al, 2019;Singh et al, 2015). It has been widely understood that adolescence is a time when many struggle with mental health, and therefore the decrease in life satisfaction scores could represent such a developmental phenomenon (Goldbeck et al, 2007).…”
Section: Life Satisfaction Decreases In Adolescencementioning
confidence: 99%
“…These findings suggested that withingroup SWB, scores decrease with age for Grade 2 and Grade 4, but not in Grade 6. Although many other research studies have reported a decreasing-with-age trend from 10 years of age on (see Casas & González-Carrasco, 2018, for a review), it typically said between age-groups, not within gradegroups, and it observed at 8 years of age in a very few countries (Casas & González-Carrasco, 2018). Perhaps this finding showed a specific phenomenon in Indonesia to explore further.…”
Section: Discussionmentioning
confidence: 89%